1989
DOI: 10.1029/ja094ia09p12021
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetic field model including magnetospheric ring current

Abstract: A quantitative model of the magnetic field in the ring current region of Earth's magnetosphere is developed by using poloidal vector fields. The magnetic field is divergence-free by construction. The main features are described by a two-term model, but a third term is necessary to describe the tilt effects. Contour plots of constant AB are in agreement with magnetometer data. Analytical expressions for the current density are derived, and the contour plots of constant J. are in topological agreement with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
(18 reference statements)
0
10
0
Order By: Relevance
“… Kosik [1989] proposed a magnetospheric model in which the magnetic field was expressed as a sum of the toroidal and poloidal terms. This representation was discussed earlier by Stern [1976], who showed that the simplest polynomial approximation of the Mead‐Fairfield model can be obtained as the sum of poloidal and toroidal fields by a proper choice of the scalar functions.…”
Section: Introductionmentioning
confidence: 99%
“… Kosik [1989] proposed a magnetospheric model in which the magnetic field was expressed as a sum of the toroidal and poloidal terms. This representation was discussed earlier by Stern [1976], who showed that the simplest polynomial approximation of the Mead‐Fairfield model can be obtained as the sum of poloidal and toroidal fields by a proper choice of the scalar functions.…”
Section: Introductionmentioning
confidence: 99%
“…Representations utilizing wire loops [Olson and Pfitzer, 1974], or flat current disks [e.g., Sugiura and Poros, 1973] contain current discontinuities while the magnetic dipole related formulations used by Tsyganenko and Usmanov [1982] and Tsyganenko [1987] result in distributed currents but lack eastward currents. In contrast, the toroidal and poloidal vector fields employed by Kosik [1989] provide a realistic representation but are too cumbersome for our purposes. We require a highly flexible yet physically reasonable system of distributed currents to control the near-Earth magnetic field.…”
Section: Jxb=vpmentioning
confidence: 99%
“…The westward current (positive) envelops the eastward current (negative) with both having their density maxima in the dipole equatorial plane. This current topology is very similar to ones derived using self-consistent methods [e.g.,Sozou and Windle, 1969] and, in particular, those produced by the AB fitting technique ofKosik [1989]. The ring current blends smoothly with the cross-tail current sheet which gradually bends away from the dipole equatorial plane to become raised by a fixed distance above the x-y plane for positive dipole tilt angles.…”
mentioning
confidence: 99%
“…For the ring current region a satisfactory description was obtained with two scalar functions for 0-tilt conditions (Kosik, 1989): give a good description of the near-Earth distortion of the magnetic ®eld through the combination of a monomial and an exponential. To take into account the tilt eects, three tilt components must be added:…”
Section: Description Of the Ring Current Magnetic ®Eldmentioning
confidence: 99%
“…The ring current region is described by three poloidal functions (Kosik, 1989). The more distant ®eld uses a vector spherical harmonics expansion and the tail model is the 1982 tail model of Tsyganenko and Usmanov (1982).…”
Section: Introductionmentioning
confidence: 99%